2021
DOI: 10.1038/s41598-021-88834-z
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress-induced somatic embryo maturation of coffee Coffea arabica L., shoot and root apical meristems development and robustness

Abstract: Somatic embryogenesis (SE) is the most important plant biotechnology process for plant regeneration, propagation, genetic transformation and genome editing of coffee, Coffea arabica L. Somatic embryo (SEs) conversion to plantlets is the principal bottleneck for basic and applied use of this process. In this study we focus on the maturation of SEs of C. arabica var. Typica. SEs conversion to plantlet up to 95.9% was achieved under osmotic stress, using 9 g/L gelrite, as compared with only 39.34% in non-osmotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Accordingly, in our experiments, somatic embryos derived from edited PEMs were induced to maturation on medium with elevated content of gelrite, in the presence of 2-iP. Under such environmental conditions, water content decreases within the SE [ 89 ]. Hence, to determine potential genes involved in embryo development and maturation, we additionally used 15-days old embryos (growing on G9-2iP medium) for RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in our experiments, somatic embryos derived from edited PEMs were induced to maturation on medium with elevated content of gelrite, in the presence of 2-iP. Under such environmental conditions, water content decreases within the SE [ 89 ]. Hence, to determine potential genes involved in embryo development and maturation, we additionally used 15-days old embryos (growing on G9-2iP medium) for RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Shoot sections (14 µm) were obtained on a rotary microtome (Reichert-Jung 2040, Leica (Hernalser Hauptstrasse, Vienna); and the root semithin sections (500 nm) with a Leica EM UC7 ultramicrotome Leica (Hernalser Hauptstrasse, Vienna). Tissue sections were stained with a 0.02% toluidine blue solution (HYCEL, Zapopan, Mexico) for 3 min, washed with distilled water for 1 min, and then air dried [86]. Shoot images were taken with a DM6000B microscope (Leica) and root photos were taken with a DMi8 inverted microscope (Leica).…”
Section: Histology Of C Citratus Shoots and Rootsmentioning
confidence: 99%
“…While the effects of low osmoticum are not fully understood, it is apparent that water limitation can induce cellular changes favoring the embryogenic and conversion processes. Recently, Valencia-Lozano et al (2021) showed that 9.0 g/L gelrite (−1.47 MPa) enhanced the conversion of Coffea arabica somatic embryos from 39% to 95% [75]. A manipulation of sucrose levels can also influence SE [25].…”
Section: Osmotic Stressmentioning
confidence: 99%